Profile of child development in Kebon Pala, east Jakarta 2021 - ., Lisnaini; Budhyanti, Weeke (International Journal Of Community Medicine And Public Health, 2023)
Background: Development is the increase in functional abilities that are more complex in aspects of gross, fine motor, language, speech and social independence. According to UNICEF in 2012, the prevalence of children with growth retardation was as high as 3 million or 27.5% of Indonesian children. Objective of this study was to find out the description of the development of children aged 0-72 months in Kebon Pala village, Makasar district, east Jakarta through early detection of development using the developmental pre-screening questionnaire (KPSP) form. Methods: This research belongs to the type of descriptive research design, which is a research method that serves to provide an overview of an object that is examined through samples collected without being analyzed and made general conclusions in September 2021-January 2022 located in the RW 011 Kebon village, Pala, Makassar district, east Jakarta. Results: Of the 96 children involved in the examination, 77 children (80.2%) with appropriate results, 12 children (12.5%) were suspected delayed development and 7 children (7.3%) facing delayed development. Conclusions: The development of children in RW 11, Kelurahan Kebon Pala, Makasar district, east Jakarta is dominated by the normal category, but still, the suspected and confirmed delayed development children were considerably high.